Included on paper, excluded in practice: or vice versa?: formal and actual target groups of Barnahus across jurisdictions - Johansson, Susanna (Justice and recovery for victimised children, 2024)
The ongoing diffusion and European standardisation of the Barnahus model has involved a general expansion of the Barnahus target group, and variations in terms of inclusion and exclusion of different groups of children, such as those who have experienced domestic violence and those who have exhibited sexually harmful behaviour. Based on policy documents, reports, standards, and regulations from Sweden, Norway, and the European policy level, this chapter analyses how the positioning of children—as aggrieved parties, vulnerable individuals, and family members—is manifested in Barnahus regulations and case processing across jurisdictions, using Sweden and Norway as in-depth cases. The chapter shows how the positioning of children affects who is granted access to Barnahus (and to which services) during the different stages of case processing.